New PSO-GWO-based model for enhancing power quality in electrical networks interconnected with photovoltaic sources - Sanaei, Mehdi; Akbari, Hamidreza; Beheshtipour, Zohreh; Mousavi, Somayeh (Frontiers in Energy Research, 2024)
This research introduces an innovative model to enhance power quality within electrical networks interconnected with photovoltaic (PV) sources. The central concern addressed in this study revolves around the impact of PV source power quality on local electric networks. This research endeavors to elucidate how achieving a more refined power pattern in electric networks is attainable by considering the power quality of PV sources. A hybrid Particle Swarm Optimization-Gray Wolf Optimization (PSO-GWO) algorithm is proposed to obtain optimal solutions. Empirical findings underscore the significant impact of Unified Power Quality Conditioners (UPQC) on social welfare, reinforcing the potential benefits of improving power quality. The results reveal that localized price reductions primarily drive the enhancement of social welfare, and this socioeconomic advantage outweighs improvements in sustainability metrics.